The Role of Digital Literature on The Sustainability of Clothing Traders in The Butung Market, Makassar City - Nurfadilah Karim; Agung Winarno; Ely Siswanto (International Journal Of Humanities Education and Social Sciences (IJHESS), 2022)
With the restrictions on community activities outside the home many people are affected, one of which is clothing traders who are in the Butung market in Makassar. Where the market is vulnerable to the potential risk of spreading COVID-19 so that some consumers decide to shop online so that buying and selling activities in the market do not run smoothly, different market conditions due to reduced visitors so that traders experience a decrease in income which will certainly affect business continuity. This study uses qualitative research using a phenomenological approach. In this study the data used were obtained from observation, in-depth interviews, and documentation, the results of the data findings were analyzed using eidetic reduction. The results show that (1) Digital literacy owned by clothing traders in the Makassar Butung market by finding the advantages of using digital media in marketing has felt the convenience provided, and is a new opportunity to increase the number of sales that do not only focus on direct sales. (offline) but also online sales. (2) Clothing traders in the Makassar Butung market who do marketing through social media have also imposed separate rules and carried out evaluations to minimize all the shortcomings that exist in marketing through their social media. (3) Utilization of social media as a support for business sustainability by providing convenience in the promotion and buying and selling process carried out by clothing traders in the Makassar Butung market who use social media to market their products and can minimize costs. (4) Clothing traders in the Makassar Butung market adapt to current technological developments in their business in the form of using social media to support the sustainability of their business and can also browse information to find what trends are now developing and can then be applied in their business.